2017
DOI: 10.3390/molecules22010143
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenolic Compounds from Hancornia speciosa (Apocynaceae) Leaves by UHPLC Orbitrap-HRMS

Abstract: Apocynaceae is a botanical family distributed mainly in tropical and subtropical regions of the world. In Brazil, they comprise about 90 genera and 850 species, inhabiting various types of vegetation. Within this large botanical family, the genus Hancornia is considered monotypic, with its only species Hancornia speciosa Gomes. Antihypertensive, antidiabetic, and antiviral activities are described for this species. Despite having been the target of some studies, knowledge of its chemical composition is still l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
1
15
0
4
Order By: Relevance
“…The identified chemical constituents that were related to the biological activities include L-(+)-bornesitol, quinic acid, chlorogenic acid, and kaempferol, quercetin, isoquercetin, rutin, and catechin flavonoids [ 4 , 5 , 11 , 13 , 14 ]. Recently, Bastos et al [ 15 ] identified other phenolic compounds, including caffeic acid, protocatechuic acid isomers, epicatechin, quercetin isomers, type-B and type-C procyanidins, coumaroylquinic acid isomers, phlorizin, phloretin, eriodictyol, luteolin, and apigenin. Natural extracts and phenolic derivatives with pharmacological potential may serve as a safe and cost-effective treatment strategy as an alternative to synthetic drugs [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identified chemical constituents that were related to the biological activities include L-(+)-bornesitol, quinic acid, chlorogenic acid, and kaempferol, quercetin, isoquercetin, rutin, and catechin flavonoids [ 4 , 5 , 11 , 13 , 14 ]. Recently, Bastos et al [ 15 ] identified other phenolic compounds, including caffeic acid, protocatechuic acid isomers, epicatechin, quercetin isomers, type-B and type-C procyanidins, coumaroylquinic acid isomers, phlorizin, phloretin, eriodictyol, luteolin, and apigenin. Natural extracts and phenolic derivatives with pharmacological potential may serve as a safe and cost-effective treatment strategy as an alternative to synthetic drugs [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the GC–MS method, the LOD is also high, and the precision and stability are poor because of the cyclic ester moiety in the PAs structure, which is easy to decompose when heated at a high temperature (Han et al , ). HPLC–MS has been proven to be a powerful and efficient tool for qualitative and quantitative analysis of PAs due to chromatographic separation performance and unequivocal identification ability (McMaster, 2005; Steinmann and Ganzera, ; Bastos et al , ). Even so, accurate quantification of micro amounts of other PAs in the herb is still missing and difficult owing to most of the PA standards being unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are responsible for color, astringency, aroma, and oxidative stability in plants (Angelo and George, 2007). Bastos et al (2017) identified seventeen compounds described for the first time for the mangaba, of which the hydroxyl fatty acids found support for antibiotic claims and the two phenylpropanoids phloretin and phlorizin and the flavonols quercetin and kaempferol support the proposed antidiabetic properties. The results demonstrate the potential of H. speciosa as a source of valuable phenolics.…”
Section: Antioxidants and Pharmacological Activitiesmentioning
confidence: 97%